An incidental latent adult hemophilia case found after a tonsillectomy. (February 2021) - Saikawa, Yuichiro; Tsunoda, Atsunobu; Sata, Naoko; Anzai, Takashi
Severe bleeding after a tonsillectomy may cause airway obstruction and be life-threatening. We report post-tonsillectomy bleeding in a 32-year-old patient with hemophilia A, who had not been aware of his disease for more than 30 years. He underwent tonsillectomy for recurrent tonsillitis. He denied episodes of bleeding tendency. The preoperative workup was normal, including platelet count, prothrombin time, and activated partial thromboplastin time. The surgery itself was uneventful, but severe bleeding from the inferior pole of the tonsillar bed developed 7 days after surgery. Emergency hemostasis was performed under general anesthesia in the operating room. The patient then remembered several episodes of bleeding tendency. Coagulation tests revealed a mild lack of coagulation factor VIII to 35%, and a diagnosis of hemophilia A was made. Hemophilia might only be found after surgery and can cause life-threatening complications. However, latent hemophilia detected after a tonsillectomy in a 32-year-old adult is very rare. A careful history of bleeding tendency is important to achieve a diagnosis of coagulopathy, perform a safer surgery, and prevent postoperative complications.